Cross-Border Mergers and Acquisitions: The Role of Private Equity Firms - Mark Humphery-Jenner; Zacharias Sautner; Jo-Ann Suchard (Tinbergen Institute, 2012)
We study the role of private equity firms in cross-border mergers and acquisitions. We find that private equity-owned firms are more likely to become targets in crossborderM&A transactions. This effect is particularly strong in transactions where the target or its shareholders actively reach out for an acquirer. On average, cross-borderdeals with private equity-involvement are not associated with higher announcement returns. However, announcement returns are higher if the acquirer is owned by a private equity firm and the target is from a country with poor corporate governance. We provide evidence indicating that the international networks and connections that result from prior cross-border deals can explain why private equity firms create value in such deals. Our findings suggest that private equity firms can help to reduce information asymmetries in certain cross-border M&A deals. We perform several tests to address possible endogeneity concerns.
Keywords: G34; G32; G24; 330; Mergers and acquisitions; private equity; information asymmetries; Übernahme; Multinationales Unternehmen; Private Equity; Eigentümerstruktur; Corporate Governance; Welt